2006
DOI: 10.1007/s10499-006-9053-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Different Hydroponic Sub-systems (gravel bed, floating and nutrient film technique) in an Aquaponic Test System

Abstract: Murray Cod, Maccullochella peelii peelii (Mitchell), and Green Oak lettuce, Lactuca sativa, were used to test for differences between three hydroponic subsystems, Gravel Bed, Floating Raft and Nutrient Film Technique (NFT), in a freshwater Aquaponic test system, where plant nutrients were supplied from fish wastes while plants stripped nutrients from the waste water before it was returned to the fish. The Murray Cod had FCR's and biomass gains that were statistically identical in all systems. Lettuce yields we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
152
5
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 224 publications
(171 citation statements)
references
References 13 publications
8
152
5
6
Order By: Relevance
“…They concluded that the floating system is cheaper in construction and maintenance, whereas the mediumbased system provides plants with added stability and can thus support larger plants. Lennard and Leonard (2006) found the NFT system to be less efficient in terms of nutrient removal and lettuce yield than the medium-based or floating raft system Schmautz et al (2016) obtained significantly lower tomato production in NFT than floating raft system but not than medium-based system. The lower nutrient removal capacity may be due to the restricted contact between the roots and the water.…”
Section: Hydroponic Systemsmentioning
confidence: 87%
See 4 more Smart Citations
“…They concluded that the floating system is cheaper in construction and maintenance, whereas the mediumbased system provides plants with added stability and can thus support larger plants. Lennard and Leonard (2006) found the NFT system to be less efficient in terms of nutrient removal and lettuce yield than the medium-based or floating raft system Schmautz et al (2016) obtained significantly lower tomato production in NFT than floating raft system but not than medium-based system. The lower nutrient removal capacity may be due to the restricted contact between the roots and the water.…”
Section: Hydroponic Systemsmentioning
confidence: 87%
“…The choice of hydroponic type for an AP system may be based on the independent advantages conferred by any particular hydroponic component (Lennard and Leonard, 2006) or on life cycle assessment impact (Forchino et al, 2017). All the methods represented in Figure 1 can be integrated in an aquaponic system (Pattillo, 2017).…”
Section: Hydroponic Systemsmentioning
confidence: 99%
See 3 more Smart Citations